Morphology and Properties of Aminosilane Grafted MWCNT/Polyimide Nanocomposites. (11th October 2007) - Yuen, Siu-Ming; Ma, Chen-Chi M.; Chiang, Chin-Lung; Teng, Chih-Chun
Abstract : This investigation presents a novel method for modifying multiwalled carbon nanotubes (MWCNTs). The morphology, electrical resistivity, and percolation threshold of MWCNT/Polyimide nanocomposites were studied. Acid-modified MWCNTs reacted with (3-aminopropyl)triethoxysilane by ionic bonding, and were then mixed with polyamic acid via imidization. TEM microphotographs reveal that silane-grafted MWCNTs were connected to each other. The electrical resistivity of silane-grafted MWCNT/polyimide decreased substantially below than that of acid-treated MWCNTs when the silane-modified MWCNT content was lower than 2.4 wt%. The percolation threshold of the MWCNT/polyimide composites is 1.0 wt% for silane-modified MWCNT and exceeds 7.0 wt% for acid-modified MWCNT. The acid-modified MWCNT/polyimide composites possess slightly higher glass transition temperatures than that of pure polyimide. The glass transition temperature of the polyimide increased significantly with silane-modified MWCNT content. Tensile properties of the polyimide have been improved with the MWCNTs content.